Hubungan Perilaku Caring Perawat Terhadap Tingkat Kepuasan Pasien Yang Di Rawat Di Ruang Rawat Inap RSUD Khidmat Sehat Afiat (KISA) Kota Depok: The Relationship of Nurses' Caring Behavior to the Level of Patient Satisfaction Treated in the Inpatient Room of Khidmat Sehat Afiat (KISA) Hospital in Depok City - Fatmawati, Ega (Indonesian Scholar Journal of Nursing and Midwifery Science, 2025)
Introduction: Caring behavior towards patients is the essence of nursing that can contribute positively to patient satisfaction in receiving nursing services. One effort to improve patient satisfaction is with good caring behavior. In reality, there are still many nurses who have not implemented caring behavior. Patient satisfaction is a level of patient feelings that arise as a result of the performance of health services obtained after the patient compares it with what is expected. Methods: The research design used a cross-sectional method. The population in this study were adult patients treated in the inpatient room of Khidmat Sehat Afiat Hospital (KISA) in Depok City. Data collection techniques used purposive sampling with a sample size of 96 respondents. The analysis used was the chi-square test.  Results: Based on the results of statistical tests with chi-square, the p-value produced was 0,000 < 0,05; which can be concluded that there is a relationship between Nurse Caring Behavior and the Level of Patient Satisfaction Treated in the inpatient room of Khidmat Sehat Afiat Hospital (KISA) in Depok City. Discussion: There is a relationship between Nurses' Caring Behavior and the Level of Patient Satisfaction Treated in the inpatient room of Khidmat Sehat Afiat (KISA) Hospital in Depok City. It is expected that health workers in the inpatient room of Khidmat Sehat Afiat (KISA) Hospital in Depok City will carry out their roles well, especially for nurses so that they can maintain a caring attitude towards all patients so that the needs, desires and expectations of patients can be meet properly. Maintaining nurses' caring behavior is very important in improving the quality of nursing services so that nurses' caring behavior needs to be improved.